Blimp-1 Contributes to the Development and Function of Regulatory B Cells - Wang, Ying-Hsiu; Tsai, Dong-Yan; Ko, Yi-An; Yang, Tsan-Tzu; Lin, I-Ying; Hung, Kuo-Hsuan; Lin, Kuo-I (Frontiers in Immunology, 2019)
Regulatory B cells (Bregs) are a B cell subset that plays a suppressive role in immune responses. The CD19+CD1dhiCD5+ Bregs that can execute regulatory functions via secreting IL-10 are defined as B10 cells. Bregs suppress autoimmune and inflammatory diseases, whereas they exacerbate infectious diseases caused by bacteria, viruses, or parasites. Notably, the molecular mechanisms regulating the development and functions of Bregs are still largely unknown. Furthermore, the biological impact of Bregs in fungal infection has not yet been demonstrated. Here, we compared the gene expression profiles of IL-10-producing and -nonproducing mouse splenic B cells stimulated with lipopolysaccharide (LPS) or anti-CD40 antibody. Blimp-1, a transcription factor known to be critical for plasma cell differentiation, was found to be enriched in the IL-10-producing B cells. The frequency of Blimp-1+ B10 cells was increased in LPS-treated mice and in isolated B10 cells that were stimulated with LPS. Surprisingly, B cell-specific Blimp-1 knockout (Cko) mice, generated by CD19 promoter driven Cre recombinase-dependent deletion of Prdm1 (gene encoding Blimp-1), showed higher frequencies of B10 cells both in the steady state and following injection with LPS, as compared with control littermates. However, B10 cells lacking Blimp-1 failed to efficiently suppress the proliferation of naïve CD4+ T cells primed with anti-CD3 and anti-CD28 antibodies. B10 cells can be stimulated for further differentiation into plasmablasts, and a subset of plasmablasts express IL-10. We found that B10 cells from Cko mice failed to generate both IL-10-nonproducing and IL-10-producing plasmablasts. Mechanistically, we found that Blimp-1 can directly suppress Il-10, whereas, in the presence of activated STAT3, Blimp-1 works together with activated STAT3 to upregulate Il-10. Moreover, we also found that B10 cells improve the clearance of Candida albicans infection but worsen the infection mortality. Notably, a lack of Blimp-1 in B10 cells did not change these effects of adoptively transferred B10 cells on fungal infections. Together, our data show that Blimp-1 regulates the generation, differentiation, and IL-10 production of Bregs.